Carotid Artery Disease Among Broadly Defined Underrepresented Groups: The All of Us Research Program. Issue 3 (3rd February 2022) - Renedo, Daniela; Acosta, Julián N.; Sujijantarat, Nanthiya; Antonios, Joseph P.; Koo, Andrew B.; Sheth, Kevin N.; Matouk, Charles C.; Falcone, Guido J.
Abstract : Supplemental Digital Content is available in the text.